2018
DOI: 10.1038/s41598-018-26138-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and diabetes distress in adults with type 2 diabetes: results from the Australian National Diabetes Audit (ANDA) 2016

Abstract: This study explores the prevalence of, and factors associated with, likely depression and diabetes distress in adults with type 2 diabetes in a large, national sample. Australian National Diabetes Audit data were analysed from adults with type 2 diabetes attending 50 diabetes centres. The Brief Case find for Depression and Diabetes Distress Score 17 were administered to screen for likely depression and diabetes-related distress, respectively. A total of 2,552 adults with type 2 diabetes participated: (mean ± S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 51 publications
9
75
3
4
Order By: Relevance
“…In addition, age and duration of DM were not significantly associated with DRD, EB, PD, RD, or ID. Previous studies have reported that DRD is associated with HbA1c [42], that EB is associated with high HbA1c levels [49], and that RD is associated with high HbA1c values in hospital [50]. The present study found that both HbA1c and co-morbidity are associated with DRD.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, age and duration of DM were not significantly associated with DRD, EB, PD, RD, or ID. Previous studies have reported that DRD is associated with HbA1c [42], that EB is associated with high HbA1c levels [49], and that RD is associated with high HbA1c values in hospital [50]. The present study found that both HbA1c and co-morbidity are associated with DRD.…”
Section: Discussionsupporting
confidence: 66%
“…showing that education has had more effect on women in relation to emotional distress. Our results are in contrast with a study which found that female gender and older age were associated with greater odds of diabetes distress [29]. The finding of our study emphasizes even more the role that health education has in reducing emotional distress and better control of glycemia in type 2 diabetic patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Diabetes distress is a common health problem which frequently co-exists with T2DM (Islam et al, 2013;Lloyd et al, 2018;Nanayakkara et al, 2018). The present study highlighted that 22.5% of men and about 55% of women were screened positive for moderate to high DRD on a DDS-17 scale.…”
Section: Discussionmentioning
confidence: 59%